LAYANAN BIMBINGAN KELOMPOK DARING BERBANTUAN APLIKASI GOOGLE MEET TERHADAP BULLYING SISWA KELAS VIII SMP ADVENT CIMINDI - Fitri Pebrimaya; Teti Sobari; Rima Irmayanti (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
Bullying is a measure of aggression that a person deriberately is bent on hurting or taking down a victim. The goal in yourtus bottom line is to increase students understanding of bullying and reduce student bullying behavior by creating online group guidance service thought the goggle meet app. Subject the list of 4 student and 1 person guidance and counseling teacher. The metodes used in this study are qualitative methods with a descriptive approach to reseach activities such as behavioral,systemic and descriptive subject such a behavior,motivational and descriptive in the form of words and balances of the natural method of inquiry and systemic,factual and accurate about the facts or situation those insidents.Keywords: Bullying , Student,Group guidance